1989
DOI: 10.1093/oxfordjournals.jbchem.a122843
|View full text |Cite
|
Sign up to set email alerts
|

Role of Outer Coat in Resistance of Bacillus megaterium Spore

Abstract: The outer coat fraction (OC-Fr) of Bacillus megaterium ATCC 12872 spore was isolated as a resistant residue after alkali extraction, sonic treatment, and pronase digestion of the spore coat preparation, and its backbone structure was determined by chemical analysis to be composed of galactosamine-6-phosphate (GalN-P) polymers with polypeptides and calcium. OC-Fr was not fully solubilized after ordinary acid hydrolysis. OC-Fr was insensitive to all hexosaminidases tested, and moreover, an isolated fragment, a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…Permeability of the exosporium is not totally surprising since germinants present in the environment have to cross the external layers of the spore to reach their receptors, albeit germinants are typically small molecules with molecular masses typically <200 Da. Additionally, the mRFP data are broadly in agreement with the results of previous studies conducted with labeled dextrans and related molecules (Koshikawa et al, 1984; Nishihara et al, 1989). In those studies, the B. megaterium QM B1551 exosporium was suggested to represent a permeability barrier to molecules with molecular weights greater than 100 KDa, while influencing the passage of molecules with masses somewhere between 2 and 40 kDa (Koshikawa et al, 1984; Nishihara et al, 1989).…”
Section: Discussionsupporting
confidence: 90%
“…Permeability of the exosporium is not totally surprising since germinants present in the environment have to cross the external layers of the spore to reach their receptors, albeit germinants are typically small molecules with molecular masses typically <200 Da. Additionally, the mRFP data are broadly in agreement with the results of previous studies conducted with labeled dextrans and related molecules (Koshikawa et al, 1984; Nishihara et al, 1989). In those studies, the B. megaterium QM B1551 exosporium was suggested to represent a permeability barrier to molecules with molecular weights greater than 100 KDa, while influencing the passage of molecules with masses somewhere between 2 and 40 kDa (Koshikawa et al, 1984; Nishihara et al, 1989).…”
Section: Discussionsupporting
confidence: 90%
“…Because our first experiments had shown that TBO appeared to bind to B. cereus spores, we washed the spores after phenothiazinium dye incubation and resuspended them in PBS before PDI. Figure 3 shows that there are three broad levels of effective- (33,35). Again, these experiments were carried out with a wash after incubation.…”
Section: Resultsmentioning
confidence: 99%
“…The function of the exosporium is unknown, but it does not appear to be important either for dormancy or germination (33). It may act as a sieving barrier, preventing exoenzymic attack on the spore coat and cortex layers (83).…”
Section: The Exosporiummentioning
confidence: 99%